Technical assessment of historic buildings on the basis of information obtained from a three-dimensional point clouds = Ocena stanu technicznego budynków zabytkowych w oparciu o dane uzyskane z trójwymiarowej chmury punktów - Pawłowicz, Joanna A.; Szafranko, Elżbieta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
3D scanning is the most modern method of unlimited possibilities based on laser technology. Its main advantage is the speed of obtaining large amounts of data in a very short time, which gives a huge advantage over existing methods of the measuring. Scanning provides opportunities for use in engineering works, geodetic and the inventory of buildings and objects of a high complexity, as well as in studies of damage or deformation of the structure. 3D scanner is a device, which with high accuracy collects data about the shape and texture of the tested object and its surroundings in the form of a point cloud.
Keywords: skaning laserowy 3D; inwentaryzacja architektoniczno-budowlana; uszkodzenia budynku; odkształcenie konstrukcji; 3D laser scanning; inventory of of architecture and construction; damage